1988
DOI: 10.1164/ajrccm/137.6.1417
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Procoagulant Activity within the Bronchoalveolar Compartment of Normal Human Lung

Abstract: The nature of the procoagulant activity of normal bronchoalveolar fluid was examined both qualitatively and quantitatively. Unconcentrated, cell-free lavage freshly obtained from normal volunteers clotted normal plasma in a mean of 84 +/- 20 s. The procoagulant activity was initiated by Factor VII-tissue factor complexes as judged by differential activity in various plasmas genetically deficient in single clotting factors, by neutralization of the procoagulant activity with antibodies to either Factor VII or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(36 citation statements)
references
References 12 publications
1
35
0
Order By: Relevance
“…The majority of the abnormalities that we previously observed in LTF mice after LPS-mediated injury (2) are recapitulated by absence of TF on the lung epithelium. These findings add to a growing literature showing that coagulation in the airspace is regulated by lung epithelial cells rather than inflammatory cells (3,9,29,31). Our group has previously reported increased levels of TF in pulmonary edema fluid of patients with acute respiratory distress syndrome compared with patients with hydrostatic pulmonary edema (3).…”
Section: Discussionsupporting
confidence: 64%
“…The majority of the abnormalities that we previously observed in LTF mice after LPS-mediated injury (2) are recapitulated by absence of TF on the lung epithelium. These findings add to a growing literature showing that coagulation in the airspace is regulated by lung epithelial cells rather than inflammatory cells (3,9,29,31). Our group has previously reported increased levels of TF in pulmonary edema fluid of patients with acute respiratory distress syndrome compared with patients with hydrostatic pulmonary edema (3).…”
Section: Discussionsupporting
confidence: 64%
“…A significant proportion of these patients develop fibrotic lesions in the terminal stages of the disease, characterized by increased mesenchymal cell proliferation and collagen deposition. Supporting, but not providing direct evidence for a role for coagulation cascade proteins in these diseases, several studies have shown that there is also increased procoagulant activity in the lungs and bronchoalveolar lavage fluid from patients with these conditions [3,4]. Similar findings have been reported for patients with chronic interstitial lung disease [5], including patients with idiopathic pulmonary fibrosis (IPF), as well as with pulmonary fibrosis associated with systemic sclerosis (SSc) [6,7].…”
Section: Involvement Of Coagulation Cascade Proteins In Interstitial mentioning
confidence: 70%
“…In previous studies, procoagulant activity attributable to components of the extrinsic coagulation pathway has been described in the alveolar compartment of man and experimental animals (2,19,21,23,(43)(44)(45)(46)(47)(48). In addition, fibrinolytic activity attributable to urokinase or urokinase-like PA has been described in BAL and macrophages from the lower respiratory tract of humans and animals (23,41,49,50).…”
Section: Discussionmentioning
confidence: 97%
“…In addition, fibrinolytic activity attributable to urokinase or urokinase-like PA has been described in BAL and macrophages from the lower respiratory tract of humans and animals (23,41,49,50). Under normal circumstances, little procoagulant activity (21,47,48) and relatively high levels of fibrinolytic activity (23, tologic hallmark of ARDS (3), and can be a prominent feature of the ILD and pneumonitides (1, 2). These observations suggest that the normal homeostasis of coagulation and fibrinolytic processes is disturbed in human lung injury and that conditions that promote fibrin deposition are established in the alveolar compartment.…”
Section: Discussionmentioning
confidence: 99%